1981
DOI: 10.1038/clpt.1981.115
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofurantoin disposition

Abstract: Nitrofurantoin (50 mg) was administered in a three-way random crossover design to six healthy men. After a 45-min intravenous infusion the plasma concentration data could be described by a two-compartment open-body model with a terminal t 1/2 of 58.1 +/- 15 min. Oral availability of a tablet was 0.87 +/- 0.13 on a fasting stomach and 0.94 +/- 0.13 when taken with food. Although absorption appeared to be complete, the absorption rate profile was complex and erratic. Two subjects failed to achieve the minimum ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…While the bioavailability of NFT in humans was approximately 90%,31 the bioavailability of NFT in rodents and rabbits was relatively low (e.g., 30% in rabbits) 32, 33. In the present study, we showed that the oral bioavailability of NFT in wild‐type female mice was 40–55% (Tab.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…While the bioavailability of NFT in humans was approximately 90%,31 the bioavailability of NFT in rodents and rabbits was relatively low (e.g., 30% in rabbits) 32, 33. In the present study, we showed that the oral bioavailability of NFT in wild‐type female mice was 40–55% (Tab.…”
Section: Discussionsupporting
confidence: 46%
“…The unbound fraction of NFT in pregnant wild‐type mice (43.6 ± 3.7%) was slightly but significantly lower than that in non‐pregnant wild‐type mice (64.4 ± 6.3%). Unbound fraction of NFT in human plasma was approximately 40% 31…”
Section: Resultsmentioning
confidence: 96%
“…Similar to rats, nitrofurantoin is well absorbed in humans (Hoener and Patterson, 1981); oral exposure and urinary excretion of nitrofurantoin is unaffected in the subjects with the ABCG2 421 AA genotype (Adkison et al, 2008). On the other hand, Abcg2 had a more pronounced effect on oral exposure of sulfasalazine in rats relative to humans.…”
Section: Discussionmentioning
confidence: 78%
“…Toxic nitrofurantoin metabolites have previously been implicated in neurologic, hepatic, and pulmonary adverse effects. 14, 15 Drug interactions due to the cytochrome P450 and/or Pglycoprotein systems are not likely the cause of our patient's hepatic and pulmonary changes. Nitrofurantoin is not known to be affected by either system, and in vitro data indicate extremely low P-glycoprotein inhibition by flu- conazole.…”
Section: Discussionmentioning
confidence: 94%